Novel triazole bearing zinc(II) and magnesium(II) metallo-phthalocyanines: Synthesis, characterization, photophysical and photochemical properties - (:unkn) unknown (ELSEVIER SCIENCE SA, 2013)
The synthesis and characterization of novel tetrakis N-(3,5-dichlorophenyl)-5-methyl-3H-1,2,4-triazol-3-one (1) and N-(3,5-dichlorophenyl)-5-ethyl-3H-1,2,4-triazol-3-one (2) substituted phthalonitrile derivatives and their new organosoluble peripherally tetra-substituted zinc(II) (6 and 7) and magnesium(II) (8 and 9) phthalocyanines were studied in this study. Photophysical and photochemical data of these compounds were measured in dimethysulfoxide (DMSO). The magnesium(II) phthalocyanine derivatives showed excellent fluorescent properties and the corresponding zinc(II) phthalocyanines generated efficient singlet oxygen. The fluorescence quenching behavior of the studied tetra-peripherally substituted zinc(II) and magnesium(II) phthalocyanine compounds by the addition of 1,4-benzoquinone were also studied in DMSO. These molecules can distinctly be employed in the field of photodynamic therapy in combination with fluorescence imaging. (C) 2013 Elsevier B. V. All rights reserved.
Keywords: Phthalocyanine; Zinc; Magnesium; Triazole; Singlet oxygen; Fluorescence; MICROWAVE-ASSISTED SYNTHESIS; METALLOPHTHALOCYANINES; SUBSTITUENTS; DERIVATIVES; MOIETIES